Efficacy evaluation of herbal preparations and antioxidants on the growth, immunity, antioxidant status and Escherichia coli counts of broilers under heat stress - RAO, M HANUMANTH; GURRAM, SRINIVAS; RAGHUNANDAN, T; KUMAR, KUNTA PRASHANTH (The Indian Journal of Animal Sciences, 2021)
The present experiment was conducted to evaluate the efficacy of different herbal preparations on the performance of broilers. For this, 250-day-old male broiler chicks were randomly divided into 5 treatment groups with 10 replicates of 5 birds each. The experimental design consisted of T1: control diet, T2: Herbal powder I, T3: Herbal powder II, T4: Herbal powder III, T5: vit E and Se. The results indicated that T4 and T5 had significantly higher body weight gain compared to other treatments at 42 d of age. However, among other test diets, cumulative body weight gain was comparable with vit E and Se. Feed intake was not influenced by different herbal supplementation, but significantly better feed conversion ratio was noticed in all the test diets. Lipid peroxidation, alkaline phosphatase, blood urea nitrogen, cholesterol, blood glucose levels and E. coli counts in small intestine were significantly low in treatment groups compared to control and at par with vit E and Se. All herbal preparations did not have any significant effect on various carcass parameters, total protein, albumin and HI antibody titer. From the results, it could be concluded that poly herbal preparations improved the overall performance of broilers.